Modelling of negative corona discharge chemistry in DRY AIR FOR A COAXIAL WIRE-TUBE ELECTRODE SYSTEM - Kwan, Alexander L. C. (My University, 1997)
Acid rain, which can damage buildings, vegetation and affect the health of animals, is produced when oxides like NOx and SOx are released into the atmosphere and react with the water vapor in air. These oxides may be produced during the combustion process in a fossil fuel fire power plant. Consequently, a number of methods have been studied to reduce the emission of these oxides from the flue gas exhaust. One of these methods is the corona discharge induced non thermal plasma technique. Corona discharge is a gas discharge in which electron, neutral radicals and ions are generated in the process. These electron, free radicals and ions will react with the oxides. The feasibility of NOx and SOx removal from the flue gas by the corona discharge method has been attempt in a number of studies. However, the mechanism behind the discharge process is still not well understood in this moment since the dominant plasma chemistry is not well investigated. In this work, a negative dc corona discharge chemistry in a coaxial wire-tube electrode configuration is numerically simulated. The purpose of this work is to try to gain a better fundamental understanding of the corona discharge process. In this model, the continuity equations and the charged (or neutral) particle transport equations are solved simultaneous with the Poisson’s equations. One hundred and ninety-five chemical reactions for 38 different chemical species are included. These species can be divided into three groups. The first group is the negative ions which includes O-, O2-, O3-, O4-, NO-, NO2-, NO3-, N2O2- and N2O3-. The second group is the neutral species which includes O, O2, O3, N, N2, NO, NO2, N2O, NO3, N2O4 and N2O5. The third group is the positive ions which includes O+, O2+, O4+, O6+, N+, N2+, N3+, N4+, NO+, NO2+, NO3+, NO4+, N2O+, N2O2+, N2O3+, N2O4+, N3O+and N4O2+. The simulation results shown that the concentrations of neutral radicals and ions (both positive and negative) increase with increasing applied voltage. The results also show that the total concentrations of the negative ions tends to increase as the radial distance from corona wire to the grounded tube electrode increases, while the contrary is true for the positive ions and the neutral radicals. Experimental results have shown that the time averaged corona discharge current increases with increasing gas flow rate. However, this increase is relatively small. Consequently, the gas flow rate have no significant effect on the concentrations of the negative ions, and negligible effect on the concentrations of the positive ions and neutral radicals when compared to the applied voltage effect. In all the simulations, the negative ion with the highest concentration is N2O2-, while the radical with the highest concentration is N2O. For the positive ion, the species with the highest concentration is N3O+ at the lower applied voltage and N2O3+ at the higher applied voltage. Also several toxic byproducts like O3, NO, NO2, N2O4 and N2O5 are observed in the simulation results. However, their maximum computed concentrations are within the acceptable limits. The neutral species observed by the present numerical simulations agree qualitatively well with Penetrante's model [1], and the experimental observations of Donohoe et al. [2], Ito et al [3], Masuda et al. [4], Hill et al. [5] and Brahdvold and Martinez [6].
MODELLING OF NEGATIVE CORONA DISCHARGE CHEMISTRY IN DRY AIR
Keywords: Fossil Fuels; Corona Discharge; Acid Rain; NOx; SOx